Meningkatkan Literasi Dan Numerasi Peserta Didik SMP Pgri 6 Surabaya Bersama Mahasiswa Kampus Mengajar Angkatan 5 - Laila Putri Hidayati; Cholis Hidayati (Universitas Kristen Indonesia Toraja, 2023)
Teaching Campus is one of the MBKM programs that seeks to provide opportunities for students to learn and develop outside the classroom. The Teaching Campus Program is in the form of instructional assistance to support the education process at the elementary and junior high levels in various villages/cities, one of which is SMP PGRI 6 SURABAYA Jl. Bulak Rukem III No.7 - 9, Wonokusumo, Kec. Semampir, Surabaya, East Java. In this program, students are responsible for supporting the learning process, technology adaptation and school administration. In addition, it is the student's task to develop student motivation and interest in learning during the assignment period. The objectives of the teaching campus program will be integrated with the outputs of this program in an effort to improve numeracy and reading skills at the elementary education level.